What are the risk factors and agents responsible for bacterial infections in ICUs? - da Silveira Silva, Francine; Brixner, Betina; de Oliveira, Caio Fernando; Pollo Renner, Jane Dagmar (O Mundo da Saúde, 2018)
This study aimed to analyze the main risk factors and prevalence of microorganisms from patients admitted in adult and neonatal ICUs. This was a retrospective study using data of microbial cultures and their respective patients admitted in adult and neonatal ICUs of a university hospital from the central region of Rio Grande do Sul, Brazil. In the adult ICU, 58.8% of patients presented heart problems, and 60 positive cultures were found with the prevalence of coagulase negative Staphylococcus (CNS) (30.0%) and Staphylococcus aureus (13.3%). In the neonatal ICU, patients predominantly presented pulmonary diseases (52.6%), and 31 positive cultures were found with the prevalence of CNS (35.5%) and Enterococcus spp. (16.1%). Thus, we conclude that both units surveyed had patients with different risk factors but with infections caused by Gram positive cocci, mainly CNS.